2021
DOI: 10.3390/v13081651
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale International Validation of an Indirect ELISA Based on Recombinant Nucleocapsid Protein of Rift Valley Fever Virus for the Detection of IgG Antibody in Domestic Ruminants

Abstract: Diagnostic performance of an indirect enzyme-linked immunosorbent assay (I-ELISA) based on a recombinant nucleocapsid protein (rNP) of the Rift Valley fever virus (RVFV) was validated for the detection of the IgG antibody in sheep (n = 3367), goat (n = 2632), and cattle (n = 3819) sera. Validation data sets were dichotomized according to the results of a virus neutralization test in sera obtained from RVF-endemic (Burkina Faso, Democratic Republic of Congo, Mozambique, Senegal, Uganda, and Yemen) and RVF-free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 70 publications
1
1
0
Order By: Relevance
“…Our study revealed varying levels of test agreement, ranging from fair to moderate (Cohen’s kappa) or almost perfect when considering PABAK. The good inter-laboratory agreement of livestock test results for RVF was in line with other studies on RVF test agreement, although it is important to note that literature is scarce [19,20]. The inter-laboratory agreement for livestock QF was slightly better than expected, based on previous studies that assessed ELISA’s agreement with different test types [15,17,18].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our study revealed varying levels of test agreement, ranging from fair to moderate (Cohen’s kappa) or almost perfect when considering PABAK. The good inter-laboratory agreement of livestock test results for RVF was in line with other studies on RVF test agreement, although it is important to note that literature is scarce [19,20]. The inter-laboratory agreement for livestock QF was slightly better than expected, based on previous studies that assessed ELISA’s agreement with different test types [15,17,18].…”
Section: Discussionsupporting
confidence: 85%
“…The use of ELISA in some studies and the gold standard test, which may differ between countries, in others can lead to discrepancies in estimated prevalence, making comparisons challenging; thus, harmonized monitoring and reporting schemes for QF and RVF have been proposed to enable consistent comparisons over time and across countries [12][13][14]. Several studies have assessed the inter-test agreement of ELISA for QF and RVF compared to other diagnostic tests, reporting variable agreement ranging from poor to good for QF and from good to excellent for RVF [15][16][17][18][19][20][21]. Diagnostic test validation can be achieved through various methods, including assessing the agreement between different tests without assuming one as the gold standard [22].…”
mentioning
confidence: 99%